KUALITAS MANUSIA DALAM PANDANGAN AL-QUR'AN - Muhammad Thaib Muhammad (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
Al-Quran is a holy book revealed to humans the prophet Muhammad through the Prophet in which there is a self-contained information about the nature and purpose of creation of the universe, and include information on the quality of man in the sight of Allah. To capture the moral messages needed wholeness of understanding, because the Qur'an It is a unity among the topics of discussion have a correlation to the topic of discussion as well. Among the important topics that revealed the Qur'an is the human quality. Human quality in view of the Koran which the author reveals here is the quality of man as a creature theoformis having a great in him, which is awarded sense to distinguish between good and bad, that led him to the highest quality as a human devoted to his Maker. In the case of the creation of human beings is not the act of God in vain. But the goal is to be a human being as a khalifa on earth. The role of the caliphate is not limited to the leaders of the community, but contains a meaning to every human being, how he set himself, the family, society and the people. Human role as a leader will be held accountable in accordance with its potential. The use of the potential that should be in accordance with the method and manner inform Allah through the Koran and sunnah of prophet.